The Management of Dhamma Retreat Affecteing Theologians’ Satisfaction at Wat Pradu Song Tham in Phranakhon Si Ayutthaya Province - treekasem, nimanong (Journal of International Buddhist Studies, 2016)
This research has the following objectives.1) to study the personal factors, behaviors when coming, opinions about the retreat’s management, and satisfaction of meditation practitioners coming to meditate at Wat Pradu Song Tham in Phra Nakhon Si Ayutthaya Province; 2) to compare the opinions of the meditation practitioners regarding the management of the dhamma retreat, classified according to personal factors and behaviors when coming to meditate; 3) compare the satisfaction of the meditation practitioners with meditating on retreat at Wat Pradu Song Tham, classified according to personal factors and behaviors when coming; and 4) to study the relationship between the opinions of the meditation practitioners regarding the management of the dhamma retreat and their satisfaction with meditating at Wat Pradu Song Tham. The sample group used in the research consisted of 384 meditation practitioners. The tool used for the research was a questionnaire using a graduated scale of 5 values, with the data analyzed statistically using percentage frequency, mean, standard deviation and hypothesis tests, as well as statistics from T-test, F-test, LSD (least. significant difference) tests and Pearson correlation coefficients determined by a level of statistical significance of .01. The results of the research found that: 1) The majority of the practitioners were male, single, aged 41-50, with the academic attainment of a diploma or higher vocation diploma, making a living as independent small businessmen earning a monthly income averaging either less than 5,000 baht or in the 10,000 - 15,000 baht range, and residing in Phra Nakhon Si Ayutthaya Province. Their main reason for coming to meditate is that they have faith in the teacher as an heir to the branch of knowledge. They come to meditate with friends twice a week on the weekends for a period of 3-4 hours. On the whole, their opinions about the the management of the retreat at Wat Pradu Song Tham, and their satisfaction meditating there are both at the highest levels. 2) Differences in gender, age, level of education, career, marital status, place of residence, behaviors when meditating and frequency of meditation of the practitioners all have an effect on opinions about the management of the retreat at Wat Pradu Song Tham. 3) Differences of age, level of education, career and frequency of meditation also have an effect on satisfaction of the practitioners with meditation at the retreat at WatPradu Song Tham. 4) The practitioners’ opinions regarding the management of the retreat correlate with their satisfaction in meditating at a low to moderate level.